Frugivores at higher risk of extinction are the key elements of a mutualistic network. Issue 12 (1st December 2014) - Vidal, Mariana M.; Hasui, Erica; Pizo, Marco A.; Tamashiro, Jorge Y.; Silva, Wesley R.; Guimarães, Paulo R.
Abstract : Most tree species rely on vertebrates for seed dispersal, and many vertebrates use fruits as food resources in tropical forests. Therefore, plant–frugivore interactions affect population dynamics and persistence in ecological communities. Plant–frugivore interactions often involve many species, forming networks of interacting plants and animals that play different roles in determining network organization. The network organization is the way interactions are structured in the community, which may have consequences for its ecological and evolutionary dynamics. Some species have greater influences on network organization and may be particularly important to species persistence. We identified the frugivores most important to the organization of networks of plants and frugivorous birds in three contiguous Atlantic forest sites in southeastern Brazil. We found that the species that contributed most to network organization were at higher risk of extinction. Among the main contributors to network organization were two cotingas and a toucan, large‐bodied species that disperse seeds from many plants and are particularly vulnerable to habitat loss and hunting. As a consequence, ongoing extinctions may significantly affect the organization of plant–frugivore interactions in the studied system. We hypothesize that the crucial role of some threatened frugivores may occur in other seed dispersal systems in tropical communities, although the association between structural importance and degree of threat may be contingent on peculiarities of local communities and disturbances.